2016
DOI: 10.1104/pp.16.01177
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Fates and Dynamic Functionalization of Young Duplicate Genes in Arabidopsis Genomes  

Abstract: Gene duplication is a primary means to generate genomic novelties, playing an essential role in speciation and adaptation. Particularly in plants, a high abundance of duplicate genes has been maintained for significantly long periods of evolutionary time. To address the manner in which young duplicate genes were derived primarily from small-scale gene duplication and preserved in plant genomes and to determine the underlying driving mechanisms, we generated transcriptomes to produce the expression profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 85 publications
2
29
0
Order By: Relevance
“…It is notable that prior studies of this type also found that conservation was one of the most common mechanisms maintaining gene duplicates in mammals and plants (Assis and Bachtrog ; Wang et al. ). In contrast, neofunctionalization was found to be the most common process maintaining gene duplicates in Drosophila (Assis and Bachtrog ).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…It is notable that prior studies of this type also found that conservation was one of the most common mechanisms maintaining gene duplicates in mammals and plants (Assis and Bachtrog ; Wang et al. ). In contrast, neofunctionalization was found to be the most common process maintaining gene duplicates in Drosophila (Assis and Bachtrog ).…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that the ancestral function of a pair of duplicates may limit their evolutionary trajectory (Wang et al. ). We also examined evolutionary and expression characteristics of duplicates that were maintained through the different evolutionary processes (Assis and Bachtrog , ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations